The Situation and Chances of Roma students in Secondary and Tertiary Education in Hungary - Csikósné Maczó, Edit; Rajcsányi-Molnár, Mónika (Central European Journal of Educational Research, 2020)
Addressing student drop-out or early school leaving has long been a major challenge for education policy makers at both national and international levels. This phenomenon affects all levels of education and has a profound impact on those classes of society that are economically and socio-culturally disadvantaged. This is particularly the case of the largest minority group in Hungary, the Roma, and its roots go back to primary education. Since the 1990s, so from the change of the regime, a positive tendency could have been observed in the completion of primary education, but in secondary school graduation and in obtaining a higher education degree they are still far behind the non-Roma population. In the current study, we identify causes of their learning failures, and we also present a selection of study grants that are available to young Roma students and support them to achieve higher levels of education. We also highlight the difficulties faced by those Roma youth, who have origins in traditional communities but obtain higher educational degrees.